Specialized Pro-Resolving Mediators Reduce Scarring After Cleft Lip Repair - Papathanasiou, Evangelos; Scott, Andrew R.; Trotman, Carroll Ann; Beale, Corinna; Price, Lori Lyn; Huggins, Gordon S.; Zhang, Yang; Georgakoudi, Irene; Van Dyke, Thomas E. (Frontiers in Immunology, 2022)
Objective: Residual scarring after cleft lip repair surgery remains a challenge for both surgeons and patients and novel therapeutics are critically needed. The objective of this preclinical experimental study was to evaluate the impact of the methyl-ester of pro-resolving lipid mediator lipoxin A4 (LXA4-ME) on scarring in a novel rabbit model of cleft lip repair. Methods: A defect of the lip was surgically created and repaired in eight six-week old New Zealand white rabbits to simulate human cleft lip scars. Rabbits were randomly assigned to topical application of PBS (control) or 1 ug of LXA4-ME (treatment). 42 days post surgery all animals were euthanized. Photographs of the cleft lip area defect and histologic specimens were evaluated. Multiple scar assessment scales were used to compare scarring. Results: Animals treated with LXA4-ME exhibited lower Visual Scar Assessment scores compared to animals treated with PBS. Treatment with LXA4-ME resulted in a significant reduction of inflammatory cell infiltrate and density of collagen fibers. Control animals showed reduced 2D directional variance (orientation) of collagen fibers compared to animals treated with LXA4-ME demonstrating thicker and more parallel collagen fibers, consistent with scar tissue. Conclusions: These data suggest that LXA4-ME limits scarring after cleft lip repair and improves wound healing outcomes in rabbits favoring the resolution of inflammation. Further studies are needed to explore the mechanisms that underlie the positive therapeutic impact of LXA4-ME on scarring to set the stage for future human clinical trials of LXA4-ME for scar prevention or treatment after cleft lip repair.